Поводження з відходами від руйнувань, що утворюються внаслідок воєнних дій: проблеми правового забезпечення (за матеріалами наукового повідомлення на засіданні Президії НАН України 10 липня 2024 р.) - Трегуб, О.А. (Вісник НАН України, 2024)
У доповіді розглянуто проблемні питання правового забезпечення поводження з відходами від руйнувань, обґрунтовано можливі шляхи їх вирішення. Наголошено на основних проблемах в організації поводження з відходами від руйнувань, що виникають на рівні регіонів і громад. Виявлено ключові недоліки та надано пропозиції щодо удосконалення правового регулювання в цій сфері. Особливу увагу приділено пропозиціям доповнити Закон України «Про управління відходами» вимогами до поводження з відходами від руйнувань, а також частково вилучити діяльність у сфері поводження з цими відходами зі сфери оцінки впливу на довкілля. The present paper concentrates on analyzing the problems of legal support for the management of demolition waste and identifying possible ways to solve them. The main problems in the organization of management of demolition waste arising at the level of regions and communities are emphasized. The paper demonstrates the shortcomings of legal regulation in the field of management of demolition waste, namely the insufficient impact of the Law of Ukraine «On waste management», discrepancies between this Law and the Procedure for managing demolition waste, violation of the principle of legal certainty and other shortcomings. Special attention is given to proposals that provide for clarifying the definition of demolition waste, supplementing the Law of Ukraine «On waste management» with requirements for the management of this waste, partial exclusion of activities in the field of demolition waste management from the scope of environmental impact assessment, and a ban on the use of components containing asbestos. The paper also proposes five directions for further research: clarification of the list and content of operations for the management of demolition waste; improvement of the procedure for identifying and accounting for this waste; tightening requirements for the treatment of hazardous components; stimulation of activities for the recycling of demolition waste and the use of its raw material potential; taking into account the specifics of this waste in planning at the state, regional and local levels.